2013
DOI: 10.1002/joc.3751
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modelling of extreme precipitation indices for the Mediterranean area under future climate change

Abstract: Projected changes of extreme precipitation in the Mediterranean area up until the end of the 21st century are analysed by means of statistical downscaling. Generalized linear models are used as downscaling technique to assess different percentile-based indices of extreme precipitation on a fine-scale spatial resolution. In the region under consideration extreme precipitation is related to anomalies of the large-scale circulation as well as to convective conditions. To account for this, predictor selection enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…The data set includes a reduced number of commonly used predictors, degraded to a common 2 grid and postprocessed by computing daily means from the original 6hourly fields when required (see Table 2). This reference data set includes most of the circulation and thermodynamic predictors at different pressure levels (including some surface predictors), typically used in downscaling applications in different European regions (Benestad, 2002;Gutiérrez et al, 2013;Hanssen-Bauer, Achberger, Benestad, Chen, & Førland, 2005;Hertig et al, 2014;Huth, 1999Huth, , 2002Huth, , 2005San-Martín et al, 2017;Timbal, Dufour, & McAvaney, 2003), excluding redundancy as much as possible. For instance, vorticity and divergence have been considered as potential predictors in the literature (see, e.g., Hessami, Gachon, Ouarda, & St-Hilaire, 2008), but they were excluded from the standard set because they reported similar results to geopotential or wind directions in some studies (Gutiérrez et al, 2013).…”
Section: Reanalysis Predictorsmentioning
confidence: 99%
“…The data set includes a reduced number of commonly used predictors, degraded to a common 2 grid and postprocessed by computing daily means from the original 6hourly fields when required (see Table 2). This reference data set includes most of the circulation and thermodynamic predictors at different pressure levels (including some surface predictors), typically used in downscaling applications in different European regions (Benestad, 2002;Gutiérrez et al, 2013;Hanssen-Bauer, Achberger, Benestad, Chen, & Førland, 2005;Hertig et al, 2014;Huth, 1999Huth, , 2002Huth, , 2005San-Martín et al, 2017;Timbal, Dufour, & McAvaney, 2003), excluding redundancy as much as possible. For instance, vorticity and divergence have been considered as potential predictors in the literature (see, e.g., Hessami, Gachon, Ouarda, & St-Hilaire, 2008), but they were excluded from the standard set because they reported similar results to geopotential or wind directions in some studies (Gutiérrez et al, 2013).…”
Section: Reanalysis Predictorsmentioning
confidence: 99%
“…In an attempt to quantify the relative contribution of each of these mechanisms to the possible evolution of extreme precipitation, Hertig et al (2014) used two general circulation models to assess the projected changes of extreme precipitation in the MR until the end of the twenty-first century by means of statistical downscaling. They found that large-scale circulation plays an important role in the generation of extreme precipitation events in the transitional seasons.…”
Section: Thermodynamic and Dynamic Predictors Of Heavy Precipitationmentioning
confidence: 99%
“…In Mediterranean regions, the most common climate change scenarios foresee an increase in temperatures and a decrease in rainfall (Christensen et al 2007;Stocker et al 2014;Giorgi and Lionello 2008;Magnan et al 2009;Gualdi et al 2013), and an increase in extreme episodes (Hertig et al 2013), with potential consequences for agricultural yields (FAO 2008) and natural resources. In this context, we must look beyond the question of sustainable development and risk and incorporate the concepts of vulnerability, adaptation, and the resilience of socioeconomic systems facing environmental change.…”
Section: A a Retrospective-prospective Analysis Of The Adaptability mentioning
confidence: 99%